Assessment of District Health System within Inter-Sectoral Context in Nepal - Bhusal CL, Singh SP, Aryal KK, Jha BK, Ghimire N, Shah N, Khatiwada D, Magar A (Journal of Nepal Health Research Council, 2013)
Background: Inter-sectoral coordination has been one of the different factors in the district health system that produces efficient output which has been identified by the Alma Ata declaration as an essential component to achieve notion of ‘Health for All’. This study was therefore aimed to describe the major four key functions of the health systems and to find out the situation of inter-sectoral coordination in Nepal.Methods: A mixed method with Focus Group Discussion (FGD) and In-Depth Interview with relevant personnel to collect the majority of the data was carried out from June 2012 to November 2012 from six districts selected purposively based on the health performance indicators.Results: The major findings in relation to the key functions of district health systems showed that the overall management of the district health system happens under the leadership of chief of District Health Office of Public health office with the cooperation of all the personnel in different sections in a predetermined pattern and inter-sectoral coordination and collaboration exist only to a very limited extent.Conclusions: The major constraints for inter-sectoral coordination to be effective is lack of its planning and enforcement where inter-sectoral coordination could be important for both preventive and promotive health care, waste management, water supply and sanitation, health service utilization, pesticides and human health, agriculture and nutrition, air pollution. The main components in the district health system needs an immediate attention and inter-sectoral effort should be initiated from the central level and implemented in all the levels.